Model and Algorithm for Rescue Resource Assignment Problem in Disaster Response Based on Demand-Ability-Equipment Matching - Xiao, Zhiwen; Wang, Guoqing; Zhu, Jianming (Queueing Theory and Network Applications, 2017)
The rapid and accurate response in post-disaster is of vital importance of emergency management. This article mainly focuses on the optimizing assignment process and aims to allocate rescue resources to diverse disaster points in an attacked area. The proposed model contains the allocation of rescue teams and equipment, and a corresponding transportation strategy was provided when the rescue team and equipment are assigned. A multi-objective optimization problem was established on the basis of cost and time consideration. Moreover, an improved epsilon-constraint algorithm was developed to find Pareto fronts of the multi-objective optimization problem. Some numerical examples are analyzed and the computational results confirm the feasibility of the assignment method.